Havanensin-type Limonoids from the Stem Bark of Chisocheton pentandrus (Meliaceae) - Dudi Runadi; Purnama Purnama; Supriatno Salam; Nulelasari Nurlelasari; Desi Harneti; Tri Mayanti; Rani Maharani; Unang Supratman; Yoshihito Shiono (Journal of Mathematical and Fundamental Sciences, 2023)
A new limonoid, belonging to the havanensin-type, called pentandricine E (1), alongside four other known types, i.e., trichilenone acetate (2), toonaciliatones C (3), 11α-acetoxyazadirone (4) and ceramicine I (5), were found in Chisocheton pentandrus stem bark. The structures of the isolated 1-5 were identified by NMR spectroscopy and HRTOFMS. Pentandricine E (1) displayed the highest cytotoxicity toward the MCF-7 breast cancer line with an IC50 value of 63.27 ± 0.21 mM.